The policy of interethnic integration in kazakhstan and theprinciples of multiculturalism (Journal of history, 2017)
In the article, issues of interethnic integration and specific features of nation building in Kazakhstan are discussed. In the focus of the research are discussions about principles of state ethno-politics, and issues of multiculturalism and interculturalism. The Article is considering how Kazakhstan is searching for its model of civilization development given multi-ethnic composition of its society.